Evaluation of different plant extracts in the management of tukra disease in mulberry caused by pinkmealybug (Maconellicoccushirsutusgreen) (International Journal of Food and Nutritional Sciences, 2022)
Tukra is one of the major problems in mulberry garden caused by pink mealybugMaconellicoccushirsutus (Green), which affects the mulberry yield. In the present study, fivedifferent concentrations [10%, 30%, 50%, 70% 90% and 100% (crude extract)] of two herbalextracts (Ocimum sanctum and Pongamia pinnata) were tested against egg hatchability,mortality of nymphs and adults and fecundity of mealybug